Factors - Factors Affecting Infertile Couple Age (EFA) Not Using Contraceptives In Hamlet II sub Desa Tanjung Anom Pancur Stone Deli Serdang regency - -, ANDRIA (Jurnal Martenity and Neonatal, 2013)
Family planning is an action that helps couples to avoid unwanted pregnancies, getting birth is very desirable, set the interval between pregnancies, controlling the time at birth in relation to the age of husband and wife as well as determining the number of children in the family, contraception is a way to prevent of conception, equipment or drugs